2007
DOI: 10.1152/japplphysiol.00618.2006
|View full text |Cite
|
Sign up to set email alerts
|

Vasoconstriction seen in coronary bypass grafts during handgrip in humans

Abstract: In animal studies, sympathetically mediated coronary vasoconstriction has been demonstrated during exercise. Human studies examining coronary artery dynamics during exercise are technically difficult to perform. Recently, noninvasive transthoracic Duplex ultrasound studies demonstrated that 1) patients with left internal mammary artery (LIMA) grafts to the left anterior descending artery can be imaged and 2) the LIMA blood flow patterns are similar to those seen in normal coronary arteries. Accordingly, subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
7
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
(30 reference statements)
4
7
1
Order By: Relevance
“…In the present report, we noted similar relative (and simultaneous) increases in CVR during handgrip exercise in both the LIMA graft and the LAD within the same individual. These vasoconstrictor responses are consistent with our recent work performed in a similar patient population (15).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In the present report, we noted similar relative (and simultaneous) increases in CVR during handgrip exercise in both the LIMA graft and the LAD within the same individual. These vasoconstrictor responses are consistent with our recent work performed in a similar patient population (15).…”
Section: Discussionsupporting
confidence: 93%
“…In the subjects that we studied, the LIMA was grafted to the coronary artery to bypass the stenosed coronary artery segments. We found that static handgrip evoked coronary vasoconstriction (15). In the present report, we speculated that vascular responses to static handgrip would be qualitatively similar in the LIMA graft and in the distal native LAD into which the LIMA graft was inserted.…”
supporting
confidence: 51%
See 3 more Smart Citations